ISLAMIC RELIGIOUS EDUCATION LEARNING POLICY AFTER COVID 19 IN MADRASAH IBTIDAIYAH AND ELEMENTARY SCHOOLS - Muhasor, Muhasor; Syafuri, B.; Wasehudin, Wasehudin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The COVID-19 pandemic has changed the education paradigm around the world, including in Indonesia. The focus of this journal is to investigate post-pandemic Islamic religious education learning policies in Madrasah Ibtidaiyah and Primary Schools. This study aims to analyse the strategies and policies adopted by these educational institutions in facing the challenges of distance learning and the implementation of health protocols. The research methods used were case studies and in-depth interviews with key stakeholders such as school principals, teachers, parents and students themselves. Data was analysed using a qualitative approach to describe the changes in learning strategies, the role of technology in teaching Islam, and the challenges and opportunities faced in the adaptation process. The results show variations in the implementation of learning policies, depending on technological infrastructure, availability of human resources and parental support. Nonetheless, Islamic religious education remains a top priority with an emphasis on religious and moral values amid the global health crisis. The implications of this study are the need for improved technological infrastructure, more intensive teacher training in online learning and the important role of families in supporting religious education at home.